Critical Discourse Analysis on Teacher Talks in The Classroom Communication - Hasanuddin Fatsah; Adriansyah Katili (Jambura Journal of English Teaching and Literature, 2020)
The research objectives were at finding out how the teacher arranges her/his teacher talk in accordance with modification to teacher speech quantity of speech, explanation, question, and error correction. This research is designed in a qualitative research approach with an etnography of communication in which the researcher gathered data about verbal communication, relying on direct observation and audio-video recording. The subjects of research were the Indonesian people who used English in communication at classroom setting. In terms of teacher talk, it is found that teachers arranged their teacher talk in acordance with (1) modification to teacher speech when giving understanding, clarifying, and simplifying their speech for developing quality of teaching and learning process, (2) quantity of speech of the teachers was limited in order to give a maximum opportunity to students in the classroom communication, (3) explanation was done to give the students theoretical knowledge, (4) question was delivered to develop indepth content and teaching material, and (5) error correction was conducted to correct students’ error in any language usage and language use.